Implementasi Metode Alamiah (Natural Method) dalam Pembelajaran Keterampilan Berbicara Berbasis Cerita di SMAN CMBBS - Mahesya Destira (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2021)
The implementation of the Natural Method in learning Arabic is very helpful for students to get the experience of learning a second language as in getting their mother tongue. Teachers in this case should not use the language of instruction. Arabic is the language used by both teachers and students in learning. The aims of this research are: first, to find out the implementation of natural methods in learning speaking skills. Second, knowing the steps for implementing natural methods in learning speaking skills. The third is knowing that story-based learning can make students easy to remember vocabulary and easy to use it in sentences. Fourth, knowing the supporting factors in the implementation of natural methods in story-based speaking skills learning. The results of the research that the natural method has been carried out but the teacher is still not consistent in learning that is still translating some sentences in Indonesian. This requires the firmness of the teacher in terms of giving meaning in the mother tongue. The spirit of students in Arabic needs to be motivated by continuing to use Arabic fluently and pleasantly.